Hamimaera thijsseni Hughes, 2016, sp. nov. - Hughes, Lauren E. (Zenodo, 2016)
Hamimaera thijsseni sp. nov. (Figs 21–23) Type material. Holotype male, 12 mm, dissected, 4 slides, SAMA C8498, northwest of West Island, Franklin Island, Nuyts Archipelago, South Australia (32°30′35″S 133°15′7″E), intertidal rock pools, 24 February 1983, coll. W. Zeidler, P. Aerfeldt and party. Paratypes 4 specimens (2 male and 2 female), SAMA C6501, northwest of West Island, Franklin Island, Nuyts Archipelago, South Australia (32°30′35″S 133°15′7″E), intertidal rock pools, 24 February 1983, coll. W. Zeidler, P. Aerfeldt and party. Type locality. Northwest of West Island, Franklin Island, Nuyts Archipelago, South Australia (32°30′35″S 133°15′7″E). Etymology. Named to honour the Dutch Captain of the Gulden Zeepeart Francois Thijssen, who accurately mapped the South Australian coast in 1627, including the Nuyts Archipelago. Description. Based on holotype male, 12 mm, SAMA C8498. Head . Eyes subovate; lateral cephalic lobe broad, rounded, apically rounded, anteroventral margin with notch/ slit, anteroventral corner subacute. Antenna 1 longer than antenna 2; peduncular article 1 shorter than article 2, with 1 robust seta on posterior margin; peduncular article 2 longer than article 3; flagellum articles as long as broad, or broader than long, with 33 articles; accessory flagellum short, significantly less than half length of primary flagellum, with 5 articles. Antenna 2 peduncular article 4 longer in length than article 5; flagellum with 11 articles. Mandible accessory setal row, well developed with 5 setae; palp well developed, article 1 length 1.1 × width, shorter than article 2; article 2 longer than article 3, with many slender setae; article 3 rectilinear, long, 3 × as long as broad, longer than article 1, with 5 apical slender setae. Lower lip unknown. Maxilla 1 inner plate subquadrate, with 3 apical plumose setae. Pereon . Gnathopod 1 coxa anterior margin concave, anteroventral corner produced, acute, posteroventral corner with notch; merus with acute posteroventral corner; carpus length 1.9 × width, 1.1 × ...